2020
DOI: 10.2147/ijgm.s279483
|View full text |Cite
|
Sign up to set email alerts
|

<p>Intracranial Primary Malignant Solitary Fibrous Tumor/Hemangiopericytoma Masquerading as Meningioma: Report of a Rare Case</p>

Abstract: Background Intracranial solitary fibrous tumors/hemangiopericytomas (SFTs/HPCs) are rare spindle cell tumors originating from interstitial tissue that are usually benign. Primary malignant intracranial SFTs/HPCs are extremely rare. Here we describe a case of malignant intracranial SFT/HPC. Case Presentation A 59-year-old woman presented with a space-occupying lesion in the left cerebellar tentorium. Based on imaging findings, we made a preoperative diagnosis of meningio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Knowledge of these tumors is crucial for neurosurgeons to include them in the preoperative differential diagnosis Figure 1 O rbital compartment syndrome (OCS) is a rare but potentially serious complication that can occur after certain neurosurgical procedures, particularly those involving the skull base and the surrounding structures, which mainly due to flap compression from frontal or frontotemporal craniotomy. [1][2][3][4] It requires quick identification and immediate treatment for preservation of vision. 2 Herein, we present an even more unusual case of bilateral OCS following a frontal craniotomy with bicoronal flap.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Knowledge of these tumors is crucial for neurosurgeons to include them in the preoperative differential diagnosis Figure 1 O rbital compartment syndrome (OCS) is a rare but potentially serious complication that can occur after certain neurosurgical procedures, particularly those involving the skull base and the surrounding structures, which mainly due to flap compression from frontal or frontotemporal craniotomy. [1][2][3][4] It requires quick identification and immediate treatment for preservation of vision. 2 Herein, we present an even more unusual case of bilateral OCS following a frontal craniotomy with bicoronal flap.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] It requires quick identification and immediate treatment for preservation of vision. 2 Herein, we present an even more unusual case of bilateral OCS following a frontal craniotomy with bicoronal flap.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…to SFT/HPC are 100% and 96.6%, respectively [21]. Karen et al [22] used 30 cases of tumors that were initially diagnosed as SFT/HPC meninges and found that all tumors expressed expression NAB2-STAT6 fusion, and it is believed that the fusion of NAB2 exon 4-STAT6 exon 3 is related to the classic SFT morphology and higher age, and shows a trend of decreased mitotic activity.…”
Section: Discussionmentioning
confidence: 99%